Identifying short-chain fatty acids originating from fermentation of plant-based foods - Shuchita, Tasnim (My University, 2025)
The concept of replacing animal-derived foods with plant-based foods (PBFs) has emerged because of the global shift towards healthier dietary patterns, sustainability, and green economy. The indigestible compounds in PBFs are fermented by the gut microbiota, generating beneficial bioactive metabolites such as short-chain fatty acids (SCFAs), which play a crucial role in maintaining gut health. While the health benefits of PBFs are well recognized, it remains unexplored how different levels of food processing influence their fermentability and the resulting SCFA production. This limitation hinders efforts to optimize food processing techniques to retain or enhance the health-promoting properties of PBFs. Therefore, this study addresses this issue by investigating how different processing levels alter the fermentation potential of soy-based products through measuring SCFAs. PBFs were selected from commercially available soy-based products- minimally processed edamame, mildly processed tofu, and heavily refined sensational burger. These were fermented in an in vitro human digestion model using a controlled bioreactor for up to 24 hours inoculated by fecal material from six volunteers. Fermented samples were collected at time points 0,1,2,4,6 and 24 hours. SCFA production was analyzed using SPME-GC-MS employing a previously established derivatization-free method. Validation was used to check the precision, linearity, and detection limits of the method prior to analysis of experimental samples. The Kruskal-Wallis Test was performed to analyze significant differences between time points across the products. The method showed good precision (RSD: 3–7.6%) and linearity (R² ≈ 0.8). Fermentation displayed minor changes for all SCFAs analyzed in minimally and mildly processed products (log₁₀-transformed signal mean area 7.6 to 8.4 A. U and 7.6 to 8.6A.U respectively), while heavily refined products displayed substantial fluctuations after 4 hours with a particularly noticeable decline in acetic acid. Propanoic acid showed minimal production (log₁₀-transformed signal mean area ranged between ~7.65 to 7.95) compared to butanoic and acetic acid across all the products. Together, the findings reflect the importance of processing techniques in maintaining plant-based materials’ biochemical composition where minimal processing could help preserve fermentation potential benefiting gut health.
Keywords: Plant-based products, Food Processing, Bio-active metabolites, Short-Chain Fatty Acids, Acetic Acid, Butanoic Acid, Propanoic Acid, SPME-GC-MS